Prunus africanus Herbal Extracts Reverse and Ameliorate the Histological and Histomorphometric Changes in Testosterone-induced Benign Prostate Hyperplasia Rat Models - William, Felix P.; Russa, Denis A. (Tanzania Journal of Science, 2021)
Benign prostatic hyperplasia (BPH) is the most common benign proliferative disease among men during aging. The herbal extract of P. africanus has been used for the treatment of BPH since time immemorial. However microstructural changes of this extract to the prostate of animal or human models are still elusive. Therefore, histological and histomorphometric changes in rats with testosterone-induced BPH due to P. africanus herbal extracts were investigated. Twenty-eight male Wistar rats (200 ± 50 g) were divided into four groups each with 7 rats. Group 1 (Negative control) was given 2 ml/day of olive oil subcutaneously and 2 ml/day of normal saline intragastrically for 28 days. Three groups were induced with BPH by subcutaneous injection of testosterone propionate 3 mg/kg body weight/day for 28 days. Thereafter Group 2 (BPH) was sacrificed, while Group 3 (Positive control) and Group 4 (Treatment group) were administered with finasteride 5 mg/kg/day and P. africanus extract 400 mg/kg/day intragastrically for 28 days, respectively. BPH group revealed thickening and hyperplasia of tubular epithelium with involutions with the stroma showing large spaces and dilated blood vessels. These features were restored with P. africanus extract administration. High epithelial height, large stromal area and lower luminal area observed in the BPH were greatly reversed with P. africanus extract comparable to negative controls. Generally, P. africanus extract restored and ameliorated histological and histomorphometrical changes of the BPH-induced rat’s prostates. Keywords: Benign prostate hyperplasia, Prunus africanus, finasteride, testosterone.